Empowerment through religion: religion’s survival strategies in democratic politics - Potz, Maciej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
In contemporary Western world religion has long lost its status of a default legitimating formula and has been relegated, in liberal political philosophy, to the private sphere. Institutionally, religious organizations have been largely separated from government institutions. Despite these adverse circumstances, religion – both as a system of ideas, values and norms and in its institutional expression – has adopted effective survival strategies guarding it from social and political marginalization. Religion has been accorded special status among other ideologies. In science, it results in a sort of methodological agnosticism, which treats religious and scientific statements as belonging to two incommensurable spheres. In politics, religious organizations are often granted special legal status among other political actors and religious freedom has been constitutionalized as a special case of general freedom of expression. As judicature and political practice show, religious arguments can often trump non-religious claims when fundamental value conflicts arise. In their political activity, religious organizations have used strategies characteristic for other political actors (lobbying, mass mobilization etc.), thereby gaining democratic legitimacy, as well as unique, religion-specific strategies. Armed with these and other empowering tools, religion can continue to influence democratic political systems in significant ways.

Utraciwszy status dominującej formuły legitymizacyjnej w świecie zachodnim, religia została też instytucjonalnie oddzielona od państwa i, w myśl ideologii liberalnej, zepchnięta na margines życia publicznego. Pomimo tych niesprzyjających okoliczności, religia – zarówno jako system idei i norm, jak i w wymiarze instytucjonalnym – zdołała obronić się przed marginalizacją, zapewniając sobie szczególny status wśród innych ideologii. W nauce objawia się to swego rodzaju metodologicznym agnostycyzmem, nakazującym traktować twierdzenia religijne jako niewspółmierne z naukowymi, a zatem niepodlegające krytyce. W polityce, organizacje religijne uzyskały w wielu państwach zachodnich szczególną pozycję, a wolność religijna została ukonstytuowana jako szczególny przypadek swobody wypowiedzi. W swej działalności politycznej organizacje religijne stosują zarówno metody identyczne z innymi aktorami politycznymi (lobbying, masowa mobilizacja itp.) – co nadaje im legitymację w ramach demokratycznych systemów politycznych – jak i specyficzne strategie religijne. Działania te są w artykule analizowane głównie na przykładach polskich i amerykańskich. Uzbrojone w takie narzędzia, religijne podmioty polityczne mogą wywierać znaczący wpływ na demokratyczne systemy polityczne.
Religia jako źródło władzy: strategie przetrwania religii w polityce demokratycznej
Keywords: religion and politics in Poland; religion and politics in USA; political science of religion; political movements; religious political actors in liberal democracy; religia i polityka w Polsce; religia i polityka w USA; politologia religii; ruchy polityczne; religijni aktorzy polityczni w demokracji liberalnej